The assessment of measurement application for timber traditional Malay house - Yusnani, Husli (2011)
The traditional Malay house serves the housing needs of the majority of people living in rural areas of Malaysia. It was evolved by the Malays over the generations, and adapted to their needs, culture, and environment. Most of the material used is readily available local material such as timber, bamboo and many more. Traditional timber houses incorporated design principals relevant in contemporary architecture such as shading and ventilation, qualities present in the basic house features. A traditional Malay timber house usually in two parts: the main house called Rumah Ibu and the simpler Rumah Dapur or kitchen annex, which was separated from the main house for fire protection. Most of the material used is readily available local material such as timber, bamboo and many more. The study was conducted in Paloh Hinai, Pahang. And the study was carried out through case study and interviews. Then the data analysis was carried out.